2012
DOI: 10.1111/j.1447-0756.2012.01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor signaling pathway involved in progestin‐resistance of human endometrial carcinoma: In a mouse model

Abstract: The present study describes an in vivo model that can provide a valuable tool in studying the interaction of overexpressed EGFR and progestin resistance in EC. Gefitinib may be useful in the treatment of progestin-resistant EC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…For example, Wnt signaling pathway, important signaling pathways in the carcinogenesis and embryogenesis, has been implicated in endometrial carcinogenesis [ 35 ]. Previous studies have demonstrated a significant correlation of EGFR overexpression with advanced stage and poor prognosis, suggesting that abnormal activation of EGFR signaling pathway contributes to tumorigenesis and metastasis of UCEC [ 36 ]. Notch signaling pathway is an evolutionally conserved developmental pathway involved in the regulation of cellular proliferation, differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wnt signaling pathway, important signaling pathways in the carcinogenesis and embryogenesis, has been implicated in endometrial carcinogenesis [ 35 ]. Previous studies have demonstrated a significant correlation of EGFR overexpression with advanced stage and poor prognosis, suggesting that abnormal activation of EGFR signaling pathway contributes to tumorigenesis and metastasis of UCEC [ 36 ]. Notch signaling pathway is an evolutionally conserved developmental pathway involved in the regulation of cellular proliferation, differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of progestin receptor (PR) resulting from continuous progestin administration leads to desensitization to progestin [ 13 ], which was thought to be one of the reasons of progestin resistance, while intermittent progestin withdrawal treatment significantly increases the apoptotic rate of endometrial cancer cells [ 14 ]. Other molecules including those in the EGF/EGFR [ 15 , 16 ] and insulin [ 9 ] signaling pathways may also contribute to progestin resistance. In our earlier studies, significant decrease of survivin expression was seen in progestin responders, whereas, no significant level changes of survivin expression were seen in non-responders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our present research, among the 24384 DEGs, we utilized the top 250 genes to conduct Functional and pathway enrichment analysis and GSEA analysis, which may provide novel insights for clarifying pathogenesis of progestin resistant. As was exhibited in DAVID, the genes were enriched in biological processes (BP) of negative regulation of DNA binding, type I interferon signaling pathway, neuron migration and axonogenesis involved in innervation, which made complementary remarks to previous points that EGF/EGFR [25] and insulin [26] signaling pathways may lead to progestin resistance.…”
Section: Discussionmentioning
confidence: 54%